2007
DOI: 10.1093/scan/nsm018
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in neural response to psychological stress

Abstract: Gender is an important biological determinant of vulnerability to psychosocial stress. We used perfusion based functional magnetic resonance imaging (fMRI) to measure cerebral blood flow (CBF) responses to mild to moderate stress in 32 healthy people (16 males and 16 females). Psychological stress was elicited using mental arithmetic tasks under varying pressure. Stress in men was associated with CBF increase in the right prefrontal cortex (RPFC) and CBF reduction in the left orbitofrontal cortex (LOrF), a rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
237
5
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(281 citation statements)
references
References 58 publications
(73 reference statements)
20
237
5
11
Order By: Relevance
“…In general, according to the results of this study, stress caused problems in various functions of visual working memory, which are consistent with the findings of other recent studies (21,22).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, according to the results of this study, stress caused problems in various functions of visual working memory, which are consistent with the findings of other recent studies (21,22).…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have reported the inhibition of working memory performance after stress (17)(18)(19)(20)(21)(22), while some have shown the improvement or lack of influence of working memory after stress (23)(24)(25)(26). The difference in the results of previous studies can be related to various factors including: type of memory (longterm memory against short-term memory), memory stage (encoding, storage, and retrieval), testing time (morning versus evening), emotional value of learned information (27,28), gender of subjects (29,30), and other factors such as age of subjects (31), one's ability to control the stressful situation (32), intensity (low, medium, or high) and the duration of exposure to the stress (33), source of stress (internal versus external), type of learning (implicit versus explicit), certain psychological properties (34), mood (35,36), personality (37), and type of individual cognitive assessment (38).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the same heightened level of math anxiety might have different effects for boys and girls, and it is crucial to understand why the relation is different. Gender differences in stress responses have been observed in adult studies, for example in the study of Wang et al (2007), where stress level was manipulated by instructing participants to do either mental arithmetic or to count backward. The observed differences seem consistent with a theory that women tend to react to stress with a so-called tend-and-befriend response, whereas men seem to be more inclined to react with a fight-andflight (competitive) response.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, genetic vulnerability has also not been considered despite a possible interactive effect between cortisol levels and apolipoproteinE allele (APOE (Lee et al, 2008). Finally, gender differences have not been examined although they have been reported in relation to both stress response and association between cortisol levels and cognitive decline and neural activity (Otte et al, 2005;Sauro et al, 2003;Seeman et al, 1997;Wang et al, 2007;Beluche et al, 2010) as well as in risk profiles for cognitive impairment and progression to dementia (Artero et al, 2008).…”
Section: Introductionmentioning
confidence: 99%